Struktur Modal dan Likuiditas Terhadap Kualitas Laba Perbankan Konvensional Indonesia - Lintang, Thoriq Aginta; Kartikasari, Evi Dwi; Mahmudah, Annita (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This research was conducted because of the background of the phenomenon of the rate of increase in profits in banking companies which is always increasing. The need for corporate profits will be able to be used optimally if the profit generated has a good level of earnings quality. Some things that are closely related to the formation of quality earnings include capital structure and liquidity. This study aims to determine the effect of capital structure proxied by DAR and DER on earnings quality, determine the effect of liquidity proxied by CR and QR on earnings quality and the simultaneous effect of capital structure and liquidity on earnings quality. This research was conducted with a descriptive qualitative method approach using multiple linear regression analysis techniques assisted by SPSS version 26. The research was conducted at Indonesian banking companies listed on the Indonesia Stock Exchange with an observation period of 2022 and 2023. The total research population was 46 companies with a total of 92 research data. The sampling technique used is total sampling. The results stated that all hypotheses proposed in this study were accepted.